Effects of a Classroom-Based Yoga Intervention on Cortisol and Behavior in Second- and Third-Grade Students: A Pilot Study. (January 2015) - Butzer, Bethany; Day, Danielle; Potts, Adam; Ryan, Connor; Coulombe, Sarah; Davies, Brandie; Weidknecht, Kimberly; Ebert, Marina; Flynn, Lisa; Khalsa, Sat Bir S.
This uncontrolled pilot study examined the effects of a classroom-based yoga intervention on cortisol concentrations and perceived behavior in children. A 10-week Yoga 4 Classrooms intervention was implemented in one second-grade and one third-grade classroom. Students' salivary cortisol responses were assessed at 3 time points. Classroom teachers also documented their perceptions of the effects of the intervention on students' cognitive, social, and emotional skills. Second, but not third, graders showed a significant decrease in baseline cortisol from before to after the intervention. Second and third graders both showed significant decreases in cortisol from before to after a cognitive task, but neither grade showed additional decreases from before to after a single yoga class. The second-grade teacher perceived significant improvements in several aspects his/her students' behavior. The third-grade teacher perceived some, but fewer, improvements in his/her students' behavior. Results suggest that school-based yoga may be advantageous for stress management and behavior.